Description of a Simple Inscribed Cross observed in the Churchyard of Tarbat and now Destroyed (Proceedings of the Society of Antiquaries of Scotland, 1915)
A dressed slab of sandstone, on one face of which was inscribed a simple cross, the arms of the cross standing between a series of symmetrically arranged circles was discovered during grave digging. It is a type which is very rare in Scotland.